Photogenerated carrier behavior at a gas–solid interface for CO2 adsorption on Cs2AgBiBr6 nanocrystals. Issue 47 (22nd November 2022) - Zhang, Rui; Li, Linjia; Tang, Bo; Wang, Dejun; Lin, Yanhong; Xie, Tengfeng
Abstract : We used a combination of in situ TPV measurements and DFT calculations for the first time to understand the carrier transfer process at a CO2 /Cs2 AgBiBr6 gas–solid interface. Abstract : Photogenerated carrier behavior at a CO2 /Cs2 AgBiBr6 quantum dot (QD) interface is investigated. In situ photovoltage spectra reveal electron transfer from the Cs2 AgBiBr6 QDs to CO2 . Moreover, this carrier transfer prefers Bi 3+ sites (over Ca + and Ag + sites) due to them exhibiting the lowest adsorption energy ( E ads = −0.125 eV) and CO2 –Bi 3+ interactions being more stable.